Between Homestay and Wetland Mangroves: A Partnership Lesson in Eco-tourism - Mohd. Yaman, Maheran; Nik Abdul Rahman, Nik Ismail Azlan (IIUM, 2009)
Abstract Kampung Perepat Timbul runs a homestay industry near Tanjung Piai Mangrove National Park, one of the largest mangrove habitats at the southernmost tip of Asian mainland. It is located in the midst of agriculture and fishing villages that can offer eco-tourism and environmental education for the visitors. It is a unique situation where the wetland mangroves are preserved and provide eco-tourism opportunities and homestay programs that could support the local economy. Efforts by the locals and the government to support local economy by proposing homestay programs initially look promising during the early establishment of the wetland mangroves However, factors such as lack of coordination, poor partnership arrangement and lack of marketing strategies have resulted in a less than successful return for eco-tourism. This paper will assess the existing partnership between these villages and the protected natural area by proposing a partnership strategy that will help to rejuvenate the eco-tourism potentials.